Case Report: Safety and Efficacy of Omalizumab in a 13-Year-Old Patient With Chronic Spontaneous Urticaria and Type 1 Diabetes - Del Barba, Paolo; Del Tedesco, Federica; Frontino, Giulio; Guarneri, Maria Pia; Bonfanti, Riccardo; Barera, Graziano (Frontiers in Immunology, 2022)
Chronic urticaria (CU) is defined by the presence of itchy wheals, sometimes accompanied by angioedema, lasting for at least 6 weeks. CU is treated with second-generation antihistamines, increased up to four times normal doses for second-line treatment. Omalizumab (a monoclonal antibody anti-IgE) may be recommended as third-line therapy in children aged over 12 years. Few reports have suggested that glucose homeostasis is impaired in some type 2-diabetic patients receiving omalizumab, and even in non-diabetic patients fasting blood glucose and HOMA-IR values appeared significantly increased. We report the case of an 12-year-old girl with diabetes mellitus type 1 (T1DM) and chronic spontaneous urticaria (CSU) refractory to standard recommended therapy that we treated with omalizumab at a standard recommended dose of 300 mg every 4 weeks. We observed a rapid and complete remission of CSU after this humanized monoclonal antibody without detrimental effects on the patient’s glucose control especially in terms of HbA1c (glycated hemoglobin), time in glycemic range (TIR) and daily insulin needs.